2014
DOI: 10.1007/s10072-014-1914-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cerebral venous thrombosis secondary to oral contraceptive use in adolescents

Abstract: Our goal was to evaluate the clinical patterns, additional risk factors, treatment and outcome of cerebral venous thrombosis (CVT) related to adolescent oral contraceptive pill (OCP) usage. We evaluated 22 patients with CVT related to OCPs admitted to Firat and Dicle University Hospitals from January 2008 to January 2013. We assessed the clinical features, risk factors, imaging results and prognosis. Magnetic resonance imaging (MRI) and magnetic resonance were the preferred procedures for the diagnosis of CVT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
2
6
0
2
Order By: Relevance
“…31 From their evaluation of 22 patients with CVT related to COC use, Özdemir et al reported that 16 patients completely recovered, and six partially recovered with some neurological deficit. 32 The CVT mortality rate was 4.8% (2/42) in our study, 1 and Bousser et al noted a mortality rate of 7.3% at the end of follow-up, 33 which was within the range reported in the literature (5.5-15%). [34][35][36] In our study, CVT was frequent, followed by DVT and/or PE among VTE, and 21.5% of CVT cases showed a poor prognosis regardless of age.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…31 From their evaluation of 22 patients with CVT related to COC use, Özdemir et al reported that 16 patients completely recovered, and six partially recovered with some neurological deficit. 32 The CVT mortality rate was 4.8% (2/42) in our study, 1 and Bousser et al noted a mortality rate of 7.3% at the end of follow-up, 33 which was within the range reported in the literature (5.5-15%). [34][35][36] In our study, CVT was frequent, followed by DVT and/or PE among VTE, and 21.5% of CVT cases showed a poor prognosis regardless of age.…”
Section: Discussionsupporting
confidence: 75%
“…From their evaluation of 22 patients with CVT related to COC use, Özdemir et al . reported that 16 patients completely recovered, and six partially recovered with some neurological deficit . The CVT mortality rate was 4.8% (2/42) in our study, and Bousser et al .…”
Section: Discussionsupporting
confidence: 73%
“…Dentro de las condiciones predisponentes para TVC, de acuerdo con lo reportado en la literatura, una condición es la de anticonceptivos orales en 54-71% de los casos aproximadamente, lo cual no difiere de lo reportado en el presente estudio (Tabla 1), seguida del embarazo y el puerperio. 1,3 En México, en 2009 se reportó que el puerperio era la principal causa predisponente para TVC. 2 Para el diagnóstico es importante mantener una sospecha clínica con especial énfasis en pacientes jóvenes que cuenten con factores de riesgo como los previamente mencionados.…”
Section: Discussionunclassified
“…Los desencadenantes crónicos de la trombosis venosa cerebral incluyen trombofilias hereditarias o adquiridas que son causas establecidas de tromboembolismo venoso. 3 Desde hace tiempo se sabe que los anticonceptivos orales están relacionados con un mayor riesgo de desarrollar tromboembolismo venoso, especialmente en pacientes portadores de defectos tromboembólicos hereditarios comunes como el factor V Leiden, el polimorfismo del factor de protrombina G20210A, la mutación MTHFR (C677T) y el polimorfismo 4G/5G del gen PAI-1, que representan la mayoría de los eventos tromboembólicos asociados con el uso de anticonceptivos orales; también, el uso de preparaciones que contienen progestinas de tercera generación, trombofilia debido a antitrombina, deficiencia de proteína C y S, factor homocigoto V (Leiden) y defectos combinados. Puede ocurrir un aumento en los niveles de factores procoagulantes, como los factores VII, X, XII y XIII, asociados con el uso de estrógenos y una reducción en los factores anticoagulantes, incluidas la proteína S y la antitrombina.…”
Section: Introductionunclassified
“…Oral contraceptives are the most common drugs responsible for causing CVST. [ 2 ] Although rare, other drugs, such as cyclosporin A and tacrolimus, have been reported to cause CVST. [ 3 ] Here, we report a rare case of CVST in a 44-year-old woman, who was administered cyclosporin A orally for 18 continuous months.…”
Section: Introductionmentioning
confidence: 99%